Production Performance of Eri Silkworm (Samia cynthia ricini) with Cassava Leaves Feed (Manihot utilissima) on Different Mountages Media - S. Putra; A. M. Fuah; Y. C. Endrawati (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
Eri silkworm (Samia cynthia ricini) is a potential silk producing insect in Indonesia. This study aimed to analyze the production performance of the S. c. ricini silkworm with cassava leaves feed (Manihot utilissima) and their cocoon productivity that mounting on different mountages (wood and carton),and also calculate the financial analysis. The silkworm was reared in altitude 176 m asl. Production performance observed were feed consumption (ingesta and digesta), larval productivity (length, breadth, and weight), and cocoon productivity (the effective rate of rearing and cocoon quality). Feed consumption and larval production were analyzed descriptively, the effective rate of rearing was compared using a t-test, cocoon quality was analyzed using a completely randomized design factorial 2 × 2 pattern. The first factor was sex and the second factor was mountages media that were used with three replications. Financial analysis was calculated using profit, R/C ratio, and BEP. The results showed the optimum consumption of cassava leaves during the study was 27.17 ± 2.39 g of feed ingestion and 19.15 ± 2.30 g of feed digestion. Mountages media did not significantly (P>0.05) influence the effective rate of rearing and cocoon quality. Cocoon weight, pupal weight, and shell ratio was affected by cocoon sex. Financial analysis calculation result showed that wood mountages gives the best value, with the profit value was Rp 21.877.819/year, R/C ratio was 1.61, BEP of yarn was 5.67 kg, BEP of eggs was 110.10 box.